Evaluasi Persepsi dan Preferensi Masyarakat tentang Pembangunan Flyover sebagai Penanganan Kemacetan di Bundaran Aloha Kecamatan Gedangan Kabupaten Sidoarjo - Ferdianto, Ardy; Rukmana, Siti Nuurlaily (Universitas Islam Sultan Agung, 2025)
The purpose of this study was to determine public perceptions and preferences regarding the Bundaran Aloha Flyover development plan, with the hope of reducing congestion. The analysis methods used include road network performance analysis, inventory, and Importance Performance Analysis (IPA) analysis. Data collection techniques were carried out through questionnaire, agency surveys, and literature studies. The results of the study showed that before the construction of ttheBundaran Aloha Flyover, the Degree of Saturation was 2.27, indicating that the level of road service was included in category F, while after the construction of the Bundaran Aloha Flyover, the Degree of Saturation decreased to 0.71, indicating that the level of road service was category C. Perceptions and preferences based on the assessment results through Importance Performance Analysis (IPA) obtained a value of 20.84 with the aspect of facilities being a priority that needs to be maintained by updating facilities such as adding pedestrian lane facilities, the availability of crossing lanes and traffic lights to facilitate and smooth the use of the Bundaran Aloha Flyover.